Comparing executive functioning and clinical and sociodemographic characteristics of people with schizophrenia who hold a driver's license to those who do not. (February 2019) - Hellinger, Nurit; Lipskaya-Velikovsky, Lena; Weizman, Abraham; Ratzon, Navah Z.
Background: Community engagement requires driving. However, there is paucity of research focusing on the potential to drive for people with schizophrenia. Purpose: This study aimed to characterize people with schizophrenia by comparing clinical signs, executive functions (EF), and sociodemographic aspects of those holding a driver's license to those without one. Method: This cross-sectional study used convenience sampling to select 60 ambulatory individuals to participate: 31 with a driver's license and 29 without one. They completed the Wisconsin Card Sorting Test (WCST) for evaluation of EF and the Positive and Negative Syndrome Scale (PANSS) for symptoms severity evaluation. Data were analyzed using multivariate analyses of covariance and logistic regression models. Findings: Participants with a license had less severe negative symptoms and general psychopathology and better EF and sociodemographic aspects compared to those without a license. Logistic regression revealed significant odds ratios (OR) in general psychopathology (PANSS; OR = 0.963, p = .011) and in the WCST (OR = 0.504, p = .027). Implications: This study offers occupational therapists a data-driven perspective on evaluating potential fitness to drive to enable participation in daily life and well-being of people with schizophrenia.